Seismic and Tsunamigenic Characteristics of a Multimodal Rupture of Rapid and Slow Stages: The Example of the Complex 12 August 2021 South Sandwich Earthquake - Metz, M.; Vera, F.; Carrillo Ponce, A.; Cesca, S.; Babeyko, A.; Dahm, T.; Saul, J.; Tilmann, F.; 1 GFZ German Research Centre for Geosciences Potsdam Germany (Journal of Geophysical Research: Solid Earth, 2022)
On 12 August 2021, a >220 s lasting complex earthquake with M w > 8.2 hit the South Sandwich Trench. Due to its remote location and short interevent times, reported earthquake parameters varied significantly between different international agencies. We studied the complex rupture by combining different seismic source characterization techniques sensitive to different frequency ranges based on teleseismic broadband recordings from 0.001 to 2 Hz, including point and finite fault inversions and the back‐projection of high‐frequency signals. We also determined moment tensor solutions for 88 aftershocks. The rupture initiated simultaneously with a rupture equivalent to a M w 7.6 thrust earthquake in the deep part of the seismogenic zone in the central subduction interface and a shallow megathrust rupture, which propagated unilaterally to the south with a very slow rupture velocity of 1.2 km/s and varying strike following the curvature of the trench. The slow rupture covered nearly two‐thirds of the entire subduction zone length, and with M w 8.2 released the bulk of the total moment of the whole earthquake. Tsunami modeling indicates the inferred shallow rupture can explain the tsunami records. The southern segment of the shallow rupture overlaps with another activation of the deeper part of the megathrust equivalent to M w 7.6. The aftershock distribution confirms the extent and curvature of the rupture. Some mechanisms are consistent with the mainshocks, but many indicate also activation of secondary faults. Rupture velocities and radiated frequencies varied strongly between different stages of the rupture, which might explain the variability of published source parameters. Plain Language Summary: The earthquake of 12 August 2021 along the deep‐sea trench of the South Sandwich Islands in the South Atlantic reached a magnitude of 8.2 and triggered a tsunami. The automatic earthquake parameter determination of different agencies showed very different results shortly after the earthquake and partially ...